Antioxidant, antimicrobial and antifungal activity of the obtained “Cachisept” tablets for resorption in the oral cavity for the treatment and prevention of dental caries - O. Yu. Maslov; M. A. Komisarenko; S. V. Ponomarenko; S. V. Kolisnyk; T. P. Osolodchenko; T. A. Kostina; Yu. S. Kolisnyk; V. P. Moroz (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2023)
Dental caries stands as a highly common chronic ailment affecting individuals globally, with susceptibility to this condition spanning their entire lifespan. Consequently, the search for novel medications aimed at treating and preventing dental caries holds significant importance in the field of pharmacy.